Health evaluation, parasite diversity and reproductive profiling in the critically endangered painted terrapin (Batagur borneoensis, Schlegel and Muller, 1844) - Kolandaiveloo, Vishwanee (2018)
Painted terrapin (Batagur borneoensis) are critically endangered, hard-shelled freshwater chelonians that inhabit rivers and estuaries of Malaysia, Brunei Darussalam, Thailand and Indonesia. The natural range of this terrapin species has reduced dramatically over the years due to pressures from environmental disturbances, habitat loss, and poaching. One of the ways to increase this species population is through captive breeding. However, there have been no successful ex situ captive breeding programmes of this species in South East Asia and this could be due to several factors like physical health, hormones, environment and nutrition. The causative factors could not be determined without conducting comparative health evaluation and reproductive profiling between captive and wild painted terrapins. Therefore the present study was conducted to evaluate the health and reproductive profile of wild B. borneoensis from Sungai Linggi, Melaka, and a captive population from a zoological facility in Melaka, Peninsular Malaysia. Blood was collected from 142 wild (50 adult male, 66 adult female, 7 sub-adult male, 11 sub-adult female, and 8 juveniles) and 12 adult (3 male and 9 female) captive painted terrapins for haematology and clinical biochemistry analyses, and monthly reproductive hormone (progesterone, oestrogen and testosterone) profiling through enzyme immunoassays (ELISA). All wild and captive painted terrapins were also subjected to morphometry, physical examination and health screening which included parasite detection and radiography. Changes in breeding colouration was monitored and scored for the males. Normal ranges for haematology and plasma biochemistry was established for the first time for wild B. borneoensis. Results indicated that the captive terrapins are in poorer health condition based on physical abnormalities, haematology, clinical biochemistry, and parasite burden compared to their wild conspecifics. This could be due to several factors such as stress of captivity, improper enclosure and poor nutrition. The most common lesions for the wild terrapins occurred on the carapace region (65.5%), while that of the captive individuals were found on the limbs (100.0%). The parasites that were encountered in this species include Falcaustra (9.4%), Orientodiscus (1.9%), Ozobranchus (30.7%), and haemogregarines (45.3%), which constitutes the first report for B. borneoensis. Helminth ova burden was more prevalent in the captive (66.7%) compared to the wild (50%) terrapins. Six wild females were found to be gravid, while only one male and one female captive terrapin showed indications of a normal breeding cycle. In the wild population, hormone profiles indicate that mating and spermiation occurs in October-November before ovulation in December- January. The breeding coloration of the wild male terrapins corresponded well with the temporal cycle of reproductive hormones. In the captive population, mating and ovulation occurs in October-November before spermiation in December-January, which explains why the eggs produced by the captive females are not fertilised. The wild population provided a baseline on the natural reproductive cycle of this species and through this study, there was asynchrony of timing between spermiation in the captive males and ovulation in the females. The reason for this hormonal imbalance could be related to suboptimal health and husbandry in captivity. It is envisaged that the data obtained will assist in the protection and conservation of this terrapin species in the wild and also assist in the management of captive individuals meant for conservation breeding in zoological facilities.